The internal structure of embryonic gonads and testis development in Drosophila melanogaster requires scrib, lgl and dlg activity in the soma - Papagiannouli, Fani (The international journal of developmental biology, 2013)
Interest in the mechanism leading to the formation of the germline and its differentiation during Drosophila development, initiated even as soon as the first ever cloned tumour suppressor gene in Drosophila, the lethal (2) giant larvae (lgl), had been identified. Further work has shown that the lgl, as well as discs large-1 (dlg) and scribble (scrib) tumor suppressor genes code for scaffolding proteins associated with either the cytoskeletal matrix or the septate junctions that act in common pathways in various tissues. This study analysed the role of Dlg, Scrib and Lgl in the embryonic gonads and testis of Drosophila melanogaster. Loss of scrib, dlg and lgl had no effect on gonad formation, but Dlg and Scrib in the gonadal mesoderm acted critically in the somatic wrapping of the pole cells and the internal structure of the Drosophila embryonic gonads. Dlg also affected the incorporation of the male-specific Sox100B positive mesodermal cells into the male embryonic gonads, yet Sox100B expression in dlg testis remained unaffected. Analysis at later stages revealed that scrib and lgl expression in the somatic lineage of the Drosophila testis, similar to what was previously shown for dlg, was indispensable for testis development and homeostasis, as depletion of these genes resulted in extensive testes defects. The data presented here emphasize the somatic requirement of Scrib, Dlg and Lgl in embryonic gonads, as well as in the Drosophila testis that underlines the importance of the somatic lineage in the establishment and maintenance of testis formation throughout successive developmental stages.